TINGKAT KEPUASAN NASABAH DITINJAU DARI FAKTOR PELAYANAN PADA PT. PEGADAIAN UNIT PELAYANAN CABANG BENGKALIS - Sari Sari; Tri Handayani (Politeknik Negeri Bengkalis, 2019)
The purpose of this research is to know the factors that affect customer satisfaction in terms of service factors in PT. Pegadaian UPC Bengkalis, The most dominant factor influencing the level of customer satisfaction in terms of service factors in PT. Pegadaian UPC Bengkalis and the smallest factor affecting the level of customer satisfaction in terms of service factors in PT. Pegadaian UPC Bengkalis. The population in this research was all customers who have never been become customers at PT. Pegadaian UPC Bengkalis and the sample were 100 respondents. The sampling technique used was purposive sampling. This type of research is associative research. The survey results revealed that the factors affecting the measurement of the level of satisfaction in terms of service factors in PT. Pegadaian UPC Bengkalis namely reliability, responsiveness, assurance, empathy and intangible. The most dominant influencing factor is Responsiveness and the smallest factor influencing that Empathy.